Inhibition of autophagy enhances effects of PF-04691502 on apoptosis and DNA damage of lung cancer cells. (September 2016) - Fei, Hong-Rong; Tian, Hua-; Zhou, Xiao-Lei; Yang, Ming-Feng; Sun, Bao-Liang; Yang, Xiao-Yi; Jiao, Peng-; Wang, Feng-Ze
Abstract: Autophagy modulation has been considered as a potential therapeutic strategy for lung diseases. The PI3K-Akt-mTOR pathway may be one of the main targets for regulation of autophagy. We previously reported that a PI3 K/mTOR dual inhibitor PF-04691502 suppressed hepatoma cells growth in vitro . However, it is still unclear whether PF-04691502 induces autophagy and its roles in DNA damage and cell death in human lung cancer cells. In this study, we investigate the effects of PF-04691502 on the autophagy and its correlation with cell apoptosis and DNA damage in non-small-cell lung cancer (NSCLC) cell lines. PF-04691502 efficiently inhibited the phosphorylation of Akt and showed dose-dependent cytotoxicity in A549 and H1299 cells. PF-04691502 also triggered apoptosis and the cleavage of caspase-3 and PARP. Phosphorylated histone H2AX (γ-H2AX), a hallmark of DNA damage response, was dramatically induced by PF-04691502 treatment. By exposure to PF-04691502, A549 cells acquired a senescent-like phenotype with an increase in the level of β-galactosidase. Furthermore, PF-04691502 enhanced the expression of LC3-II in a concentration-dependent manner. More interestingly, effects of PF-04691502 on toxicity and DNA damage were remarkably increased by co-treatment with an autophagy inhibitor, chloroquine (CQ), in human lung cancer cells. These data suggest that a strategy of blocking autophagy to enhance the activity of PI3 K/mTOR inhibitors warrants further attention in treatment of NSCLC cells.